Governing disturbance regimes: rewilding and the management of large herbivores in UK nature conservation - Soares, FF (2020)
In recent years, there has been a rethinking of the role of disturbance regimes in nature conservation: from exceptional and destructive events to be controlled and/or avoided, to key ecological processes to be nurtured and choreographed. These regimes concern the spatiotemporal dynamics of ecological disturbances, understood here as events that disrupt the structure of an ecology, community or population, causing profound changes in an ecosystem. The rethinking of their role precedes but resonates with current enthusiasms for proactive and experimental modes of conservation, such as rewilding.